An empirical examination of factors driving the offshore renminbi market. Issue 3 (2nd September 2017) - Burdekin, Richard C. K.; Tao, Ran
ABSTRACT: Following the 2010 establishment of the offshore renminbi market in Hong Kong, renminbi deposits there quickly rose above RMB 1 trillion. In this article, we examine fluctuations between the offshore value of the renminbi in Hong Kong and its onshore value in mainland China. The size of the spot market spread appears to be influenced by stock market sentiment as reflected in the spread between A-shares listed in Shanghai and H-shares listed in Hong Kong. There is also some evidence of a link between the spread and the pace of renminbi deposit growth in Hong Kong.